High hair cortisol concentrations predict worse cognitive outcome after stroke: Results from the TABASCO prospective cohort study. (August 2017) - Ben Assayag, E.; Tene, O.; Korczyn, A.D.; Shopin, L.; Auriel, E.; Molad, J.; Hallevi, H.; Kirschbaum, C.; Bornstein, N.M.; Shenhar-Tsarfaty, S.; Kliper, E.; Stalder, T.
Highlights: Higher hair cortisol concentrations were significantly associated with a larger lesion volume. Higher hair cortisol concentrations were significantly associated with worse cognitive results 6, 12 and 24 months post-stroke. Individuals with higher long-term cortisol release (higher hair cortisol concentration) are prone to cognitive decline following an acute stroke or transient ischemic attack. High HCC possibly modulate the response to cerebral ischemia and may serve as a preclinical marker of dementia. Abstract: Background and purpose: The role of stress-related endocrine dysregulation in the development of cognitive changes following a stroke needs further elucidation. We explored this issue in a longitudinal study on stroke survivors using hair cortisol concentrations (HCC), a measure of integrated long-term cortisol levels. Methods: Participants were consecutive cognitively intact first-ever mild-moderate ischemic stroke/transient ischemic attack (TIA) survivors from the Tel Aviv Brain Acute Stroke Cohort (TABASCO) study. They underwent 3T magnetic resonance imaging (MRI) scanning and were cognitively assessed at admission, and at 6, 12 and 24 months post-stroke. Scalp hair samples were obtained during the initial hospitalization. Results: Full data on baseline HCC, MRI scans and 2 years neuropsychological assessments were available for 65 patients. Higher HCC were significantly associated with a larger lesion volume and with worse cognitive results 6, 12 and 24 months post-stroke on most of the neurocognitive tests. 15.4% of the participants went on to develop clinically significant cognitive decline in the follow-up period, and higher HCC at baseline were found to be a significant risk factor for this decline, after adjustment for age, gender, body mass index and APOE e4 carrier status (HR = 6.553, p = 0.038). Conclusions: Our findings suggest that individuals with higher HCC, which probably reflect higher long-term cortisol release, are prone to develop cognitive decline following an acute stroke or TIA.